MOTIVASI DAN KINERJA PEGAWAI NEGERI SIPIL DI KECAMATAN PAJAR BULAN - Ruaman Yudianto (Fakultas Ekonomi dan Bisnis Islam, 2023)
This study aims to examine and analyze the motivation and performance of Civil Servants in the Pajar Bulan District. The results showed that the motivation given to employees in Pajar Bulan Subdistrict, Lahat Regency influenced employee performance such as individuals, organizations, and psychology. The coefficient value of 0.197 is relatively small but has a positive influence on the performance of Civil Servants in Pajar Bulan District, Lahat Regency. The internal motivation of each Civil Servant in the Pajar Bulan Subdistrict, Lahat Regency is greater than the given External Motivation. To improve the motivation and performance of sub-district employees, researchers suggest giving more tasks and delegation of authority to further increase the internal motivation of each employee. It is better if the superior understand the individual employees better to find out what kind of motivation should be given. Provide awards, greater achievement opportunities with agencies, and provide promotions to employees who have good work performance.